Relationship between Usage of E-Wallet towards Firm Performance among SME Company in Batu Pahat, Johor - Goh Hui Mei,; Mohd Zarir Yusoff, (Research in Management of Technology and Business, 2024)
An alternate payment method for buying products and services is the electronic wallet, which is part of the new technology. Due to contemporary times, Malaysia has begun to adopt cashless transactions like other nations have done. There are still difficulties in integrating the technology, even though numerous establishments have begun to provide cashless payment options. As a result, there is a correlation between e-wallet usage and corporate performance. A questionnaire was the data collection tool employed in this study's quantitative research design. 136 supervisors from the company who responded to the survey received it. A statistical package for the social sciences. This study's drawback is that it was restricted to Batu Pahat. As a result, it is impossible to extrapolate the findings of this study to the company performance of customers in other markets who utilize e-wallets. Consumer watchdogs and later researchers can make use of the study's findings to improve the drawbacks of e-wallets.